Cost performance and change management capability level of contractors: a relational quantitative study - Ajayi, Arowosegbe Augustine (2015)
Project changes are very common and inevitable; hence they constitute high level of risk that contributes to projects failure. However, project change cost is observable to be one of the most sensitive aspects of construction project management and it is also one of the most difficult to control. It has been recognized that higher capability maturity levels leads to better and consistent performance and that projects that adopts change management capability maturity level as a criterion for contractor’s pre-qualification incurs lower costs overrun on project budgets. Therefore, examining the relationship between the change management capability maturity level of contractors and cost performance of building projects is the focus of this research. Adopting a questionnaire survey, data collected from respondents were analyzed using importance index, fuzzy synthetic evaluation, spearman’s rank correlation and multiple regression to investigate the impact which overall CMCML of contractors will have in mitigating project cost overrun. The research findings reveal that the project cost overrun is negatively related to CMCML of contractor as evidenced by the co-efficient of determination R 2=–0.305 (i.e., as CMCML increases, project cost overrun decreases). In addition, the result further indicates that there is a strong negative relationship between CMCML and project cost overrun going by the spearman’s rank correlation coefficient value of -0.618. The established model is capable of predicting contractors’ CMCML thus making it possible to forecast contractor’s likelihood of performance in terms of cost. Moreover, the developed model will enhance easy elimination of incompetent contractors prior to contract award thus creating a fairer competition among contractors.